Aggregate Productivity and Heterogeneous Firms - Erling Holmøy; Torbjørn Hægeland (Statistics Norway, Research Department, 2000)
It is an established fact that firms, even within narrowly defined industries, differ with respect to productivity. In this paper we analyse how observed heterogeneity in productivity is affected by endogenous producer behaviour, and to what extent shifts in firm specific productivity parameters will affect aggregate industry productivity. We find that endogenous producer behaviour and equilibrium adjustments may strongly affect observed productivity of firms and aggregate industry productivity. This makes it problematic to interpret them as structural parameters. The main lesson from the paper is that identification of such parameters should rely on structural models, in which the equilibrium determinants of observable productivity for individual firms, the distribution of output shares over firms, and the number of firms are taken into account. One may otherwise draw very misleading conclusions about changes in structural parameters from observed productivity variations, either between firms or for an industry over time.
Keywords: D24; L11; 330; Productivity; Heterogeneity; Aggregation